ICWA global review 2023 (New Delhi KW Publisher, 2024)
ook The Indian Council of World Affairs regularly brings out insightful and quality research articles in the form of Issue Briefs and View Points on major political, security and economic trends and developments in Asia, Africa, Europe, the United States, Latin America, Oceania and the wider global geostrategic and economic environments. These research articles contribute to foreign policy debates and discussions on a regular basis. This publication ICWA Global Review 2023 comprising research papers by the Research Faculty of ICWA focuses on global and regional developments in the year 2023. The articles capture the key developments in various geographies, their impact and implications. ICWA The Indian Council of World Affairs (ICWA) was established in 1943 by a group of eminent intellectuals led by Sir Tej Bahadur Sapru and Dr. H.N. Kunzru. Its principal objective was to create an Indian perspective on international relations and act as a repository of knowledge and thinking on foreign policy issues. The Council today conducts policy research through an in-house faculty as well as through external experts. It regularly organises an array of intellectual activities including conferences, seminars, roundtable discussions, lectures and brings out a range of publications. It has a well-stocked library, an active website and publishes the journal India Quarterly. ICWA has over 50 MoUs with international think tanks and research institutions to promote better understanding on international issues and develop areas of mutual cooperation. The Council also has partnerships with leading research institutions, think tanks and universities in India.
Keywords: International Relation; Foreign Relation; World Affairs; ICWA